The Effect of Mixing Red Coconut and Green Coconut on The Manufacture of VCO Using The Centrifugation Method - Nadya Permata Kamila; Wisnu Broto (Journal of Applied Food Technology, 2022)
Virgin coconut oil (VCO) can be made from several types of coconuts by using several techniques that potentially result ini clear colour, distinct coconut smell, and long shelf life. In this study, centrifugation method was used in the manufacture of VCO by using green coconuts and red coconuts with a ratio of 1:1 and 2:1. This study aims to determine the ratio of the best raw materials and determine the % yield. This study uses factorial design and a quicker method for calculating the effect of the process variable with eight runs (experimental). The most influential variable was the centrifugation time, where the optimum yield was 35 minutes, the centrifugation speed was 800 rpm, and the ratio of green coconut and red coconut was 4:3. yielded 56.8% yield. It can be concluded that the best way to produce VCO with a high yield is to use a centrifugation method with a ratio of green to red coconuts of 4:3, a centrifugation time of 35 minutes, and a centrifugation speed of 800 rpm.